THE POTENTIAL OF TOURISM VILLAGE AND COMMUNITY EMPOWERMENT IN PANGKALAN INDARUNG VILLAGE, SINGINGI DISTRICT, KUANTAN SINGI REGENCY - Salsa Dila Oktaviani; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT In this research using descriptive qualitative research methods, there is a goal to find out how the Potential of Tourism Villages in Community Empowerment in Pangkalan Indarung Village, Singingi District, Kuantan Singingi Regency, describes the role of tourism in community empowerment. Based on the results of the research that has been done, there are results that show the Potential of Pangkalan Indarung Village Tourism Village has attractions, namely Natural and Cultural attractions. Natural attractions include rivers, plantations, Mamucuak, rice fields. While the cultural attractions are Pacu Barge, Manggiliang Tobu, Balimau Kasai. Tourism that grows among the Pangkalan Indarung village community is very good for increasing the economy and income of the community itself, and for advancing Pangkalan Indarung Village as a Tourism Village. In general, tourism is concerned with the plantation economy, local cultural traditions such as Manggiliang Tobu, Balimau Kasai Mamucuak, Pacu Barge. Keywords: Potential, Tourism, Empowerment, Community.